2014
DOI: 10.1007/s11033-014-3672-x
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate lyase is required for urediniospore germination of Puccinia striiformis f. sp. tritici

Abstract: The PstICL1 gene, which encodes isocitrate lyase, a key enzyme in the glyoxylate cycle, was cloned and characterized in the biotrophic wheat pathogen Puccinia striiformis f. sp. tritici (Pst). Expression analyses of PstICL1 exhibited high levels of transcripts in ungerminated urediniospores, which showed low isocitrate lyase enzyme activity. In planta, PstICL1 expression was continuously down-regulated upon germination. During the later stages of the infection of wheat, the level of PstICL1 expression was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Our observation showed that heterologous expression of MlpHog1 in FgHog1 mutant did not fully complement the defects on environmental stresses, sexual reproduction and plant infection, which is similar to the phenomenon that PstMAPK1 and PstILC1 from Puccinia striiformis partially complemented the defects of corresponding ascomycetous mutants (Guo et al 2011;Liu et al 2014). Based on the bioinformatics analysis, the intact Hog1 pathway is present in M. larici-populina and MlpHog1 displays the high degree of conservation.…”
Section: Discussionmentioning
confidence: 57%
“…Our observation showed that heterologous expression of MlpHog1 in FgHog1 mutant did not fully complement the defects on environmental stresses, sexual reproduction and plant infection, which is similar to the phenomenon that PstMAPK1 and PstILC1 from Puccinia striiformis partially complemented the defects of corresponding ascomycetous mutants (Guo et al 2011;Liu et al 2014). Based on the bioinformatics analysis, the intact Hog1 pathway is present in M. larici-populina and MlpHog1 displays the high degree of conservation.…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with the high levels of PsCS1 transcripts, high CS enzyme activity was detectable in the germinated urediniospores compared with the nongerminated urediniospores. Before haustoria form, Pst is dependent upon the lipids stored in urediniospores, which are then converted into carbohydrates by the glyoxylate cycle for development (Liu et al, 2014). In addition, the TCA cycle also becomes more active to satisfy the energy requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA extraction and cDNA synthesis were performed as previously described (Liu et al, 2014). The expression levels of PsCS1 were assayed at different Pst infection stages by qRT-PCR as previously described (Liu et al, 2016).…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected candidate genes are most often assayed by HIGS to validate their involvement in pathogenicity through quantitative estimation of infection‐related traits. Depending on the given candidate, different complementary approaches were applied, such as subcellular localization in heterologous systems or in wheat protoplasts (Cheng et al ., , ; Wang et al ., ; Zhu et al ., ,b), complementation assays on yeast or fungal pathogens (Guo et al ., ; Liu et al ., ; Liu J. et al ., ; Zhu et al ., ), yeast invertase secretion assays (Cheng et al ., ; Liu J. et al ., ; Wang et al ., ), plant cell death BAX‐triggered suppression assays (Cheng et al ., ,b; Liu J. et al ., ) and overexpression in yeast coupled with the monitoring of stress responses (Cheng et al ., , ; Tang et al ., ,b; Jiao et al ., ; Zhu et al ., ,b). Among the proteins characterized through the aforementioned pipeline, six were identified as protein kinases or regulators of kinases in fungal transduction pathways (Guo et al ., ; Jiao et al ., ; Cheng et al ., , ; Qi, Zhu et al ., ) whereas others corresponded to a mitochondrial adenine nucleotide translocase antiporter (PsANT; Tang et al ., ,b), a superoxide dismutase (Liu J. et al ., ), an isocitrate lyase required for spore germination and one transcription factor.…”
Section: Functional Characterization Of Rust Effectorsmentioning
confidence: 99%